Dwór obronny w Proboszczewicach koło Płocka - Marciniak-Kajzer, Anna (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
The so-called motte at the village of Proboszczewice was excavated in 1989-1990. The earliest reference to the village dates from 1375 when the Plock bishop Dobiesław Sówka of Gulczew (1375-1381) founded it under German law. It seems probable that the village was not founded in cruda radice but that new rights and organization forms were given to an already existing earlier settlement. It was the property of the Płock chapter and later belonged to the state-owned estate of Brwilno. The name of Proboszczewice appears often in archaeological literature on account of the huge early medieval ring-earthwork located near the village. It was only m 1988 that the second earthwork, conical in shape, was discovered in the centre of the village, some 60 m away from the manor house of the early 20th century. The rather steep mound rises some 6.5 m above the meadow level and its oval plateau measures 20 by 16 m. The excavated area of 86.4 m2 has yielded 2968 finds, mostly potsherds and oven tiles as well as several dozen iron objects (boltheads, a spearhead, various fittings, a key, staples, nails). The investigations show that the earth for the mound was taken from a dry moat which out off part of the promontory on the upland side. Remains of two habitation phases: late medieval and modem, have been found. In the second half of the 14th century a timber building of palisade construction, later destroyed by fire, existed in the southern part of the plateau. About the middle of the 15th century a house of block construction was built nearby. In the second part of the 16th and in the first part of the 17th century the motte was not occupied. The second phase of occupation lasted from the second part of the 17th century to the end of the 18th. The building of that period was also of timber and had no cellars. However, two tile ovens have been ascertained there.